Carrying extra state with callback functions - Beazley, David M.; Jones, Brian K. 1973- (O'Reilly Media, Inc., 2024)
Build your knowledge of Python, the world's favorite programming language, with this Shortcuts collection. These recipes address a range of well-known and more advanced function definitions, as well as common programming patterns for class and object definitions.
Keywords: Python (Computer program language); Programming languages (Electronic computers); Python (Langage de programmation)